Kajian Literatur : Hubungan Kepemimpinan, Manajerial Kepala Sekolah, dan Kemampuan Teknologi dengan Kinerja Guru SMK - Adrita Gusdila; Ernawati Ernawati; Jonni Mardizal (Departement of Mathematics Education, 2024)
This study aims to examine the influence of leadership, managerial skills, and mastery of technology of the principal on teacher performance in Vocational High Schools (SMK). This study uses a descriptive method with a qualitative approach through analysis of literature studies from various previous studies. The results of the study indicate that the leadership of the principal has a significant influence on teacher performance, especially through motivation, professional support, and the creation of a conducive work environment. The managerial skills of the principal, which include planning, organizing, and supervision, also have a positive impact on teacher efficiency and professionalism. Although the principal's mastery of technology does not directly affect teacher performance significantly, technology still contributes to supporting administrative tasks and encouraging learning innovation. The combination of these three aspects of leadership, managerial, and technology can create an educational environment that supports improving teacher performance and the quality of learning in SMK. Thus, this study strengthens the importance of the strategic role of the principal in optimizing teacher performance in order to achieve educational goals that are relevant to the needs of the world of work.